2020
DOI: 10.2174/1573399815666191024085838
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes and its Impact on the Immune System

Abstract: Introduction:: Type 2 Diabetes (T2D) is a major health problem worldwide. This metabolic disease is indicated by high blood glucose levels due to insufficient insulin production by the pancreas. An inflammatory response occurs as a result of the immune response to high blood glucose levels as well as the presence of inflammatory mediators produced by adipocytes and macrophages in fat tissue. This low and chronic inflammation damages the pancreatic beta cells and leads to insufficient insulin production, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
665
2
18

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 726 publications
(697 citation statements)
references
References 72 publications
12
665
2
18
Order By: Relevance
“…Indeed, HbA 1c levels were associated with neither the composite primary outcome nor the death rate [23]. Such results may seem surprising as chronic hyperglycaemia has long been known to damp down the immunological defences of diabetes patients [18,27]. However, caution is still required, as HbA 1c measurements were missing in about one-third of the studied population.…”
Section: Role Of Diabetic Complications and Glucose Controlmentioning
confidence: 92%
See 1 more Smart Citation
“…Indeed, HbA 1c levels were associated with neither the composite primary outcome nor the death rate [23]. Such results may seem surprising as chronic hyperglycaemia has long been known to damp down the immunological defences of diabetes patients [18,27]. However, caution is still required, as HbA 1c measurements were missing in about one-third of the studied population.…”
Section: Role Of Diabetic Complications and Glucose Controlmentioning
confidence: 92%
“…In the largest series of 5700 patients hospitalized with COVID-19 in New York City in the US, it was only mentioned in passing that, of the patients who died, those with diabetes were more likely to have received invasive mechanical ventilation or care in the ICU compared with those without diabetes, with no further information provided regarding the characteristics of those diabetes patients [17]. One key question is whether diabetes is a risk factor for COVID-19 infection and poorer outcomes because of the deleterious role of hyperglycaemia on immune responses and defence against infections [18], the multiple complications associated with diabetes, especially CVD and/or renal disorders, and the comorbidities frequently encountered, such as obesity, hypertension and obstructive sleep apnoea, in the type 2 diabetes (T2D) patient population [19]. Furthermore, the potential interference of certain medications frequently prescribed for diabetes patients are also worthy of attention [19,20]: renin-angiotensin-aldosterone system (RAAS) blockers have been suspected to facilitate intracellular penetration of SARS-CoV-2 [21]; and dipeptidyl peptidase (DPP)-4 inhibitors can interfere with the immune response [22].…”
Section: Introductionmentioning
confidence: 99%
“…Several explanations of the association between diabetes and worse clinical can be proposed [18]. In general, patients with diabetes are more susceptible to a wide range of infections because of alterations in neutrophil chemotaxis, cytokine production and impaired T-cell responses as a consequence of hyperglycemia [19][20][21]. With this regard a recent study clearly showed that diabetic patients experienced a delayed clearance of SARS-CoV-2 [22].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Hexoskin repurposed biometric shirts that are capable of continuously measuring vital signs, including temperature, respiration effort, and cardiac activity, to better understand the evolution of COVID-19 and its effects on lung function [39]. The use of data from glucometers among patients with diabetes could also be used as an objective indicator of infection, as high glucose levels correlate with signs and symptoms of infection [40]. Infectious respiratory diseases, such as COVID-19, have the potential to worsen symptoms of pre-existing lung disease, and thus exacerbate the use of emergency medications.…”
Section: Monitoringmentioning
confidence: 99%